Optimizing and Controlling the Productivity of a Flat Plate Collector by Using an Electronic System. (February 2017) - Anoune, Kamal; Bouya, Mohsine; Abdellah, Abdellatif Ben; Astito, Abdelali
Abstract: The Flat Plate Collector (FPC) is a thermal solar collector used in housing or residential applications that allows the conversion of solar radiation to thermal energy (e.g. hot water). In this paper we propose a new approach that improves the hot water production through the combination between a simple and improved architecture model. The optimization of the thermal energy efficiency is guaranteed by using an electronic architecture that controls the mono-axial tracker. Some experimental tests aiming the comparison between the stationary and improved FPC are presented.